Prevalence and risk factors of mood and anxiety disorders in children and young people: Findings from the Northern Ireland Youth Wellbeing Survey. (July 2022) - Bunting, Lisa; Nolan, Emma; McCartan, Claire; Davidson, Gavin; Grant, Anne; Mulholland, Ciaran; Schubotz, Dirk; McBride, Orla; Murphy, Jamie; Shevlin, Mark
Objective: This paper presents the key findings from the Northern Ireland Youth Wellbeing Prevalence Survey (NIYWS), specifically the prevalence of common mental health disorders and their association with personal, familial and socio-economic risk factors. Methods: The Northern Ireland Youth Wellbeing Survey (NIYWS) is a large nationally representative household survey of young people aged 2–19 years (N = 3074) and their parents (N = 2816). Data collection was by means of a stratified random probability household survey. Children and young people were eligible to take part if they were aged 2 to 19 and lived in Northern Ireland. Mood and anxiety disorders were measured using the Revised Children's Anxiety and Depression Scale (RCADS: Chorpita et al., 2000). Results: Based on the cut-off scores for the RCADS 11.5% of the sample met the criteria for any mental health disorder. The most prevalent disorder was panic disorder (6.76%) and the least common was generalised anxiety disorder (2.69%). Poor child health, special educational needs, parental separation, living in a household in receipt of benefits, living in an area of deprivation and living in an urban area were all significant predictors of any mood or anxiety disorder. Conclusions: The results indicate somewhat elevated prevalence rates of mood and anxiety disorders in children and young people in Northern Ireland compared to England and other international countries. These findings can be used to help inform mental health policy and practice.